Screening the past : film and the representation of history - Barta, Tony, 1942- (Praeger, 1998)
Addressing the various ways the past is ""screened"" for our understanding and relating the art of film to other media, this collection of essays deals with the changing perspectives of political and social development in films and television programmes made for historically shaped reasons.